2015
DOI: 10.1038/tp.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Total serum cholesterol, atherogenic indices and their longitudinal association with depressive symptoms among US adults

Abstract: Serum cholesterol, both total and lipoprotein fractions, has been associated with mid- and late-life depression. Using longitudinal data on a large and ethnically diverse sample of urban adults, the associations of serum lipid profile measured by high or low total cholesterol (TC; >200 mg dl−1; <160 mg dl−1) and by atherogenic indices, namely high total cholesterol and low-density lipoprotein cholesterol relative to high-density lipoprotein cholesterol, with change in total and domain-specific depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 83 publications
(196 reference statements)
3
25
0
Order By: Relevance
“…Lower level of HDL is associated with higher atherogenicity and risk for cardiovascular disease [ 90 , 114 ]. Atherogenesis is frequently accompanied by depression in women [ 49 ]. Lowered serum level of HDL is detected also in depression, especially in patients with suicidal attempts [ 113 ] and with postpartum depression.…”
Section: Effect Of Antioxidants Micronutrients and Vitamins In Dmentioning
confidence: 99%
“…Lower level of HDL is associated with higher atherogenicity and risk for cardiovascular disease [ 90 , 114 ]. Atherogenesis is frequently accompanied by depression in women [ 49 ]. Lowered serum level of HDL is detected also in depression, especially in patients with suicidal attempts [ 113 ] and with postpartum depression.…”
Section: Effect Of Antioxidants Micronutrients and Vitamins In Dmentioning
confidence: 99%
“…Initially, we found that the levels of TC, LDL‐C, and HS‐CRP decreased significantly in the ATV groups compared with the control group after 8‐week of ATV treatment, indicating that a proper dose of ATV could promote vascular endothelial function. Serum cholesterol, either total or lipoprotein fractions, is in closely association with human both mid‐ and late‐life depression . A cohort study was conducted for determining the relative risk and incidence for myocardial infarction, and it verified that TC was a significant risk factor for myocardial infarction .…”
Section: Discussionmentioning
confidence: 88%
“…Serum cholesterol, either total or lipoprotein fractions, is in closely association with human both mid-and late-life depression. 21 A cohort study was conducted for determining the relative risk and incidence for myocardial infarction, and it verified that TC was a significant risk factor for myocardial infarction. 22 LDL-C level is strongly associated with sustained viral response for chronic hepatitis C infection, and it was concluded that LDL-C burden might identify those patients with pegIFN/RBV therapy.…”
Section: Discussionmentioning
confidence: 90%
“…When these indices increase, the risk of cardiovascular disease increases [47, 51, 52]. The administration of fruit extract to rats at three doses significantly reduced all of the atherogenic indices.…”
Section: Discussionmentioning
confidence: 99%